SODIUM AESCINATE INJECTION FOR SKIN FLAP TRANSPLANTATION OF HAND OR FOOT IN CHILDREN - Liyou, Wei; Zhikui, Liu; Hongwei, Zhang; Guoqian, Wang (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: The purpose of this study is to evaluate the efficiency and safety of sodium aescinate injection for treating children suffering transplanted flap in children hand or foot. Materials and Methods: Ninety children patients with transplanted cutaneous nerve nutrition vascular flaps in hand or foot were selected and divided into “treatment” and “control” groups randomly by computer. The treatment group was prescribed intravenous sodium aescine injection and conventional therapy. The control group was only offered conventional therapy. Seven days following treatment, cumulative wound drainage, swelling of flap and adverse reactions were recorded. One month subsequent to treatment, two-point discrimination of flap was recorded. At the outset of treatment (0-d) and 1, 3, 7-days following treatment, the concentrations of C-reactive protein (CRP) and malondialdehyde(MDA) in venous blood were tested. Results: At the outset of treatment, there was no statistically significant difference between the two groups in terms of CRP and MDA (P>0.05). At 3 and 7 day intervals following treatment, the concentrations of CRP and MDA in treatment group were lower than those in control group (P<0.05). The treatment Group’s wound drainage, swelling of flap and two-point discrimination of flap was better than those recorded in control group (P<0.05). Conclusion: Sodium aescine injection can improve the concentrations of CRP and MDA in venous blood, reduce wound drainage, and promote flap sensory recovery. This has an effective and safe application for treating children with swelling in their hands or feet.